Thermal and Anti-inflammatory Activities of Silver Nanoparticles (AgNPs) by Using Leucas aspera Leaves Extracts. - Fazle Rabbi Shakil Ahmed; Md. Abu Bakkar; Rubaiyat Farzana Hussain; Md. Ali Akbar; Md. Najem Uddin; Mst. Jesmin Sultana (Nanochemistry Research, 2025)
This investigation focused on the thermal and anti-inflammatory properties of AgNPs successfully synthesized from Leucas aspera extract and characterized using scanning electron microscopy (SEM), Fourier transform infrared (IR), X-ray diffraction (XRD), and ultraviolet-visible spectroscopy (UV-Vis). A peak in absorption was detected in the UV-visible spectra of the aqueous media containing silver nanoparticles at about 480 nm. The reduction and capping of silver nanoparticles were caused by biomolecule molecules, as demonstrated by IR spectra. The particles were shown to be crystalline and had a face-centered cubic (fcc) structure using XRD analysis. AgNPs' clustered and irregular morphologies, which were primarily aggregated, were clearly visible in the SEM study, and their average size was 50 nm. Synthesized AgNPs' in vitro anti-inflammatory characteristics revealed that the inhibition of protein denaturation at 73%, 93% and 96% at concentrations of 250µg/ml, 500µg/ml and 750µg/ml, respectively. TGA/DTA results confirmed the weight loss and the exothermic reaction due to desorption of chemisorbed water. However, the thermal stability and anti-inflammation abilities of silver nanoparticles obtained from Leucas aspera leaf extract are described for the first time in this article.